Numerical Solution of the Mathematical Model of DHF Spread using the Runge-Kutta Fourth Order Method - Side, Syafruddin; Zaki, Ahmad; Miswar (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
This research was conducted to find a numerical solution to the mathematical model of DHF in Makassar using the Runge-Kutta fourth order method. The mathematical model of DHF is in the form of a system of differential equations that includes variables S (Susceptible), E (Exposed), I (Infected), and R (Recovery) simplified into classes of vulnerable (S), exposed (E), infected (I) and cured (R) as initial value. Parameters value that is solved numerically using the Runge-Kutta fourth order method with time intervals h = 0.01 months using data from South Sulawesi Provincial Health Service in 2017. Based on the initial value of each class, namely: obtained (Sh1) =10910.4, (E) = 0, (Ih1) = 177.9 , (Sv1) = 5018685.6, (Iv1) = 135.4, and R = -981612.3. The initial values ​​and parameter values ​​are substituted into numerical solutions to the model simulated using maple as a tool.